The formation and development of the legislation on legal regulation of the relations in the sphere of increase of fertility of soils - Хомінець C. B. (Theory and practice of jurisprudence, 2016)
Article is devoted to research of a question of legal regulation of the public relations in the sphere of increase of fertility of soils, since times of Kievan Rus’. Stages of development of the legislation of rather legal support of increase of soils are analysed.